Pengaruh Misalignment Terhadap Arus Listrik dan Putaran Poros pada Komponen Transmisi Sproket dan Rantai - Romiyadi Romiyadi; Yudi Dwianda; Widya Sinta Mustika (Universitas Muhammadiyah Yogyakarta, 2023)
The sprocket and chain transmission system was used to transmit the rotating force that occurs between two shafts where they can reach it. The sprocket and chain transmission system transfers a movement from the driving source to the moved object. If the maintenance of the sprocket and chain transmission system is carried out only occasionally, the sprocket and chain may cause misalignment. That can affect the machine's performance and cause a breakdown of the machine's components. This study aims to determine the effect of misalignment on the electric current usage and shaft rotation speed in the sprocket and chain transmission system. The leading equipment used in this study is a sprocket and chain alignment kit, while the auxiliary equipment used are ampere meter, tachometer, and other equipment. Measurements of electric current and shaft rotational speed were carried out with a variation of misalignments. The study results show that the increase in the misalignment causes a higher electric current. As for the effect of misalignment on shaft rotational speed, the rise in the misalignment causes the post-rotational rate to lower.